The Role of the Ngunduh Tradition in the Conservation of Swallow's Nests in Karangbolong Village, Kebumen Regency of Central Java, Indonesia - Supriyati, Hikmah (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The Ngunduh tradition of swallow's nest is a tradition that has been passed down from generation to generation by people in Karangbolong Village, Buayan District Kebumen Regency. This ritual tradition is carried out so that the implementation of taking swallow's nest runs smoothly and avoid disaster. According to the myth that circulates, taking swallow's nest without ceremony or ritual will result in accidents and even death. The purpose of this study is to determine the Role of Ngunduh Tradition in Conservation of Swallow's Nests in Karangbolong Village, Buayan District, Kebumen Regency of Central Java, Indonesia. This study uses a qualitative method with a literature study approach. Apart from that, to support the data, interviews were also conducted with people who have been involved in taking swallow's nests. Based on the results of interviews and literary studies that have been conducted, the concept of conservation already exists in the tradition of taking swallow's nest. The Ngunduh tradition that has been preserved by the community will have a positive impact on the existence of swallows in Karangbolong. The belief in the Ngunduh ceremony before harvesting swallow's nest is a myth that is very useful in preserving nature. This tradition will be a part of the life of the local community because it is accompanied by spiritual beliefs and strengths related to the existence of swallow's nest in Karangbolong cave.